Bangladesh Agricultural Value Chain (AVC) Impact Evaluation: Baseline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Funded under the Feed the Future (FTF) Initiative, the Bangladesh Agricultural Value Chains (AVC) project being implemented by Development Alternatives International (DAI) is working to improve food (and nutrition) security through strengthened agricultural value chains. The dataset comprises information gathered from a baseline survey of farmer households in rural districts in southern Bangladesh. The sample was composed of 1,000 households primarily growing a food crop (mung bean) and 1,000 household growing a non-food crop (jute). The survey collected information on: demographics; agricultural production and marketing; assets, expenditures and consumption, and women’s empowerment in agriculture.